Targeting trafficking as a therapeutic avenue for misfolded GPCRs leading to endocrine diseases - Ulloa-Aguirre, Alfredo; Zariñán, Teresa; Gutiérrez-Sagal, Rubén; Tao, Ya-Xiong (Frontiers in Endocrinology, 2022)
G protein-coupled receptors (GPCRs) are cell surface membrane proteins associated with an array of functions. Mutations in these receptors lead to a number of genetic diseases, including diseases involving the endocrine system. A particular subset of loss-of-function mutant GPCRs are misfolded, trafficking defective receptors unable to traffic through the secretory pathway to reach their site of function (i.e. the cell surface plasma membrane). Endocrine disorders in humans caused by GPCR misfolding include hypo- and hyper-gonadotropic hypogonadism, morbid obesity, familial hypocalciuric hypercalcemia and neonatal severe hyperparathyroidism, X-linked nephrogenic diabetes insipidus, congenital hypothyroidism, and familial glucocorticoid resistance, among others. Several in vitro and in vivo experimental approaches have been employed to restore function of some misfolded GPCRs linked to endocrine disfunction. The most promising approach is by employing pharmacological chaperones or pharmacoperones, which serve as molecular frameworks to assist misfolded mutant proteins to fold properly and adopt a more stable, minimal free-energy conformation to pass the scrutiny of the cell’s quality control system, thereby correcting misrouting. This review covers the most important aspects that regulate folding and traffic of newly synthesized proteins, as well as experimental approaches targeted to overcome protein misfolding, with special focus on GPCRs involved in endocrine diseases.